Diagnosis of functioning pancreaticoduodenal neuroendocrine tumors. (26th January 2015) - Imamura, Masayuki; Nakamoto, Yuji; Uose, Suguru; Komoto, Izumi; Awane, Masaaki; Taki, Yoshiro
Abstract Functioning pancreaticoduodenal neuroendocrine tumors (PD‐NETs) are popular in a textbook, but they are still unfamiliar to a general clinician, and delay of diagnosis or misdiagnosis has been reported even today. It is a consensus that sporadic functioning PD‐NET is cured only by surgical resection. So, early detection and early resection is the gold standard for the treatment of functioning PD‐NET. Functioning PD‐NETs in patients with multiple endocrine neoplasia type 1 (MEN 1) are often multiple. You should check about MEN 1 whenever you encountered multiple PD‐NET. They are diagnosed in younger age than sporadic cases. In most cases they are accompanied with numerous microscopic or macroscopic nonfunctioning P‐NETs, which are potentially metastatic and the most common cause of death in MEN 1 patients. © Japanese Society of Hepato‐Biliary‐Pancreatic Surgery